Modulated expression of the HIV-1 2LTR zinc finger efficiently interferes with the HIV integration process. Issue 5 (7th September 2018) - Moonmuang, Sutpirat; Saoin, Somphot; Chupradit, Koollawat; Sakkhachornphop, Supachai; Israsena, Nipan; Rungsiwiwut, Ruttachuk; Tayapiwatana, Chatchai
Abstract : Lentiviral vectors have emerged as the most efficient system to stably transfer and insert genes into cells. By adding a tetracycline (Tet)-inducible promoter, transgene expression delivered by a lentiviral vector can be expressed whenever needed and halted when necessary. Here we have constructed a doxycycline (Dox)-inducible lentiviral vector which efficiently introduces a designed zinc finger protein, 2-long terminal repeat zinc-finger protein (2LTRZFP), into hematopoietic cell lines and evaluated its expression in pluripotent stem cells. As a result this lentiviral inducible system can regulate 2LTRZFP expression in the SupT1 T-cell line and in pluripotent stem cells. Using this vector, no basal expression was detected in the T-cell line and its induction was achieved with low Dox concentrations. Remarkably, the intracellular regulatory expression of 2LTRZFP significantly inhibited HIV-1 integration and replication in HIV-inoculated SupT1 cells. This approach could provide a potential tool for gene therapy applications, which efficiently control and reduce the side effect of therapeutic genes expression.